Persuasive Features in @Mohon Clash (Please Break) Twitter Account - Radzuwan, Ab Rashid; Nurul Kamilah, Malip; Nur Fatihah, Hassan (2016)
This paper is a study on persuasive features in a Social Networking Sites, @Mohon Clash (Please Break) Twitter account. It analyzes which elements under the Aristotelian theory: ethos, pathos and logos that are often used by the curator to persuade the followers as well as other users. The data consist of 250 postings found in @Mohon Clash (Please Break) Twitter account. ( within the three months period in 2015). This paper considers the language style used by the curator to approach other twitter users by giving out his ideas and thought in a unique and interactive language and which is absolutely out from formality. Analysis shows that logos is the most preferable elements use by the curator of this account. However, pathos is the one that gives the most impact to the readers. So this paper will reveal the reasons on preference elements and also the feedback given.